2021
DOI: 10.3389/fneur.2021.649749
|View full text |Cite
|
Sign up to set email alerts
|

Iatrogenic vs. Spontaneous Preterm Birth: A Retrospective Study of Neonatal Outcome Among Very Preterm Infants

Abstract: Objective: Preterm birth is a leading contributor to childhood morbidity and mortality, and the incidence tends to increase and is higher in developing countries. The aim of this study was to analyze the potential impact of preterm birth in different etiology groups on neonatal complications and outcomes and to gain insight into preventive strategies.Methods: We performed a retrospective cohort study of preterm infants less than 32 weeks' gestation in the Third Affiliated Hospital of Zhengzhou University from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 37 publications
0
14
2
Order By: Relevance
“…24 In addition, the Canadian study enrolled singleton deliveries only, which might have impacted on the study outcomes. 24 The prevalence of spontaneous preterm birth in the current study was inconsistent with studies conducted in Birmingham, Alabama, USA (67.3%), 25 Brazil (62.4%), 26 Third Affiliated Hospital of Zhengzhou University, China (61.5%), 27 Addis Ababa (66.1%) 14 and Lusaka, Zambia (68.9%). 28…”
Section: Discussioncontrasting
confidence: 88%
See 1 more Smart Citation
“…24 In addition, the Canadian study enrolled singleton deliveries only, which might have impacted on the study outcomes. 24 The prevalence of spontaneous preterm birth in the current study was inconsistent with studies conducted in Birmingham, Alabama, USA (67.3%), 25 Brazil (62.4%), 26 Third Affiliated Hospital of Zhengzhou University, China (61.5%), 27 Addis Ababa (66.1%) 14 and Lusaka, Zambia (68.9%). 28…”
Section: Discussioncontrasting
confidence: 88%
“…24 In addition, the Canadian study enrolled singleton deliveries only, which might have impacted on the study outcomes. 24 The prevalence of spontaneous preterm birth in the current study was inconsistent with studies conducted in Birmingham, Alabama, USA (67.3%), 25 Brazil (62.4%), 26 Third Affiliated Hospital of Zhengzhou University, China (61.5%), 27 Addis Ababa (66.1%) 14 and Lusaka, Zambia (68.9%). 28 The likelihood of a having spontaneous preterm birth among mothers without a partner was almost twice that of mothers with a partner (AOR ¼ 1.470, 95% CI 1.23, 4.42; P ¼ 0.037) in the current study.…”
Section: Discussioncontrasting
confidence: 88%
“…Despite advances in the care of newborns, intraventricular hemorrhage (IVH) remains a common complication in preterm infants, especially in those <32 weeks' gestation ( 1 ). The overall incidence of IVH is about 36% in preterm infants ( 2 ), and the incidence of IVH increases as gestational age and birth weight decrease ( 3 ).…”
Section: Introductionmentioning
confidence: 99%
“…Preeclampsia/eclampsia and IUGR were more significantly associated in the medically indicated group as compared to the spontaneous group. A Chinese study too revealed hypertensive disorder as the most common indication for early pregnancy termination in the iatrogenic group (72.8%), followed by fetal distress and placental abruption [ 27 ]. There was no significant difference in the frequency of antepartum haemorrhage between the spontaneous and iatrogenic groups in our study.…”
Section: Discussionmentioning
confidence: 99%